The recreational sports activities in teens of the community "Sabana" - Guillermo Rosselló-Legra (Universidad de Guantánamo, 2014)
The use of free time by teens in the community Sabana of the municipality Maisí is a need of our times, which is why this work is intended to solving this problem through recreational sports activities. The fact that to the teens sports recreational activities are not frequently offered was revealed in a diagnosis, and they get involved in other activities, so it was necessary to create a system of activities that contribute to occupying the free time of these adolescents. The assessment allows the specialists affirming that the system of proposed actions is feasible.